SPECIES COMPOSITION OF FISH FAUNA IN THE COASTAL WATERS OF QUANG NGAI PROVINCE - Thao, Le Thi Thu; Quang, Vo Van; Vu, Nguyen Phi Uy (Vietnam Journal of Marine Science and Technology, 2018)
Three surveys were carried out in May, August and December 2014 at 7 sampling location to determine species composition of fish fauna in the coastal waters of Quang Ngai province (the Central Vietnam). A total number of 178 species of fishes were identified belonging to 125 genera, 68 families and 13 orders. Analysis of community structure of fish fauna showed that Perciformes order was the most popular, making up 71.9%; Tetraodontiformes (8.4%); Pleuronectiformes (5.6%). Serranidae family was the most abundant with 14 species, making up 7.9% of the total number of species; Carangidae: 12 species (6.7%); Lutjanidae, Gobiidae had the same number of species with 9 species (5.1%); Scombridae: 7 species (3.9%); Soleidae: 6 species (3.4%); Haemulidae, Mullidae, Tetraodontidae: 5 species (2.8%);... Cluster analysing based on the Bray-Curtis similarity index of nine fish faunas (Thai Binh, Son Tra, Thu Bon, Quang Nam, Nha Phu-Binh Cang, Ben Tre and Tra Vinh) showed that fish composition of the coastal estuaries of Tra Vinh and Ben Tre had the highest similarity (80%), subsequently fish fauna of Quang Ngai had similarity with that of Nha Phu-Binh Cang (39%), Quang Ngai and Quang Nam (42%), Quang Nam and Nha Phu-Binh Cang (41%), Quang Nam and Son Tra (38%), Thai Binh and Ben Tre (37%), Quang Ngai and Son Tra (36%). The result was also classified into two distinct groups of 7 fish faunas: Group 1-Tra Vinh, Ben Tre and Thai Binh; group 2-Quang Ngai, Quang Nam, Nha Phu-Binh Cang and Son Tra. The species richness (Margalef’s index) of Quang Ngai (34.2) was less abundant than other areas, the highest species richness belonged to Tra Vinh (38.2), Thai Binh (38.0), Quang Nam (37.8), Nha Phu-Binh Cang (35.1), Son Tra (30.9), Ben Tre (29.4). The diversity of species composition according to the level taxa in each region showed the characteristic of each fish fauna.